SYSTEMATIC LITERATURE REVIEW: DETERMINANTS OF EMPLOYEE PERFORMANCE IN SOUTHEAST ASIA FROM A THEORY OF PERFORMANCE (TOP) PERSPECTIVE - Baiq Risfa Ermianti; Karina Dewi Saefitriana; M. Kusuma Atmaja; Santi Nururly (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Employee performance is a key driver of organizational effectiveness in Southeast Asia, a region marked by rapid economic change and diverse institutional contexts. Although numerous empirical studies have examined performance determinants in this region, existing findings remain fragmented and lack integration within a comprehensive theoretical framework. This study addresses this gap through a Systematic Literature Review (SLR) grounded in the Theory of Performance (ToP). Following PRISMA 2020 guidelines, ten Q1–Q3 empirical articles published between 2015 and 2025 from Vietnam, Indonesia, Malaysia, and Thailand were systematically analyzed. The synthesis indicates that organizational context—particularly high-performance work systems, strategic human resource practices, and talent management—serves as the primary foundation of employee performance. Internal states, especially employee engagement, consistently function as the central mechanism translating contextual support into performance outcomes, including task performance and innovative behavior. Individual capability contributes to performance but operates optimally only when supported by favorable contexts and psychological conditions. Cross-country analysis further reveals contextual variation, with commitment and job satisfaction dominating bureaucratic settings, while engagement and proactive behaviors are more salient in adaptive, knowledge-intensive sectors. This review provides the first integrative ToP-based synthesis of employee performance in Southeast Asia and offers implications for context-sensitive human resource strategies.